La structure profonde et la modélisation des règles de construction de lexèmes: l'exemple de cinq suffixes agentifs du français - Owoeye, Samuel Tuesday (Linguistik Online, 2014)
The advent of the Chomskyan Lexicalist Hypothesis brought about radical theoretical orientations in the field of morphology. One of those orientations is Lexeme-Based Morphology. Primarily, morphologists under the auspices of Lexeme-Based Morphology formulate and describe rules that generate built lexemes. Having observed that most of the morphological rules hitherto formulated revolve most essentially around syntactic rules, we set out in this paper to explore few principles of D-structure of language in the formulation of a rule that can account for the construction of all possible agent nouns arising from five French suffixes (-ant, -eur, -ier, -iste and -oir). We adopt the substratal principle whereby the formation of lexemes is organized around a multidimensional operation which takes into account graphemic, phonological, syntactic and semantic information about both the base and the built lexemes.